The death of Jesus in early Christianity - Carroll, John T. 1954-; Green, Joel B. 1956- (Peabody MA Hendrickson, 1995)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- criticism, interpretation, etc; Jesus Christ -- crucifixion -- history of doctrines -- early church, ca. 30-600.; Bible. N.T. -- extra-canonical parallels